Biological Recovery Of Pha From Bacterial Cells Using Mealworms (Tenebrio molitor) And Black Soldier Fly Larvae (Hermetia illucens) - Sivakumar, Lilyann Narishah (2025)
The production of polyhydroxyalkanoates (PHA) can be upscaled through fermentation and be chemically and biologically recovered from the bacterial cells to produce valuable plastic wares. PHA can be chemically recovered by using chloroform, but it is hazardous and costly. For biological recovery, the bacterial cells must be dry prior, to be a suitable insect feed through freeze-drying or drum-drying. These drying processes are not environmentally friendly, thus, hindering the commercial productions of PHA.